Efektivitas Pendekatan Student-Centered Learning dalam Meningkatkan Kepercayaan Diri Mahasiswa dalam Proses Pembelajaran - Aulia Luthfiyyah; Dealova Despita Maharani; Elga Desvita; Nenden Risya Aulia (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
Student-Centered Learning (SCL) is a learning approach that is centered on students, in this approach educators act as facilitators in the learning process. This approach focuses on the active involvement of students in the teaching and learning process, encouraging them to build their own knowledge through exploration, discussion, and collaboration. Therefore, the author conducted a study on how the Student-Centered Learning approach can increase student self-confidence. The research method used is a quantitative research method with a questionnaire as the main instrument for collecting data. The questionnaire was compiled using a Likert scale, which allows respondents to provide an assessment of various statements related to the effectiveness of the student-centered approach in learning. The majority of students support the implementation of Student-Centered Learning because it increases their confidence in speaking, asking questions, expressing opinions, completing academic assignments, and helps overcome feelings of insecurity through discussion methods and group work.